The ALMA Survey of Gas Evolution of PROtoplanetary Disks (AGE-PRO). I. Program Overview and Summary of First Results - Ke Zhang; Laura M. Pérez; Ilaria Pascucci; Paola Pinilla; Lucas A. Cieza; John Carpenter; Leon Trapman; Dingshan Deng; Carolina Agurto-Gangas; Anibal Sierra; Nicolás T. Kurtovic; Dary A. Ruiz-Rodriguez; et al. (The Astrophysical Journal)
We present the Atacama Large Millimeter/submillimeter Array Survey of Gas Evolution of PROtoplanetary Disks (AGE-PRO), a large program of the ALMA. AGE-PRO aims to systematically trace the evolution of gas disk mass and size throughout the lifetime of protoplanetary disks. It uses a carefully selected sample of 30 disks around M3-K6 stars in three nearby star-forming regions: Ophiuchus (0.5–1 Myr), Lupus (1–3 Myr), and Upper Sco (2–6 Myr). Assuming the three regions had similar initial conditions and evolutionary paths, we find the median gas disk mass appears to decrease with age. Ophiuchus disks have the highest median gas mass (6 M _Jup ), while the Lupus and Upper Sco disks have significantly lower median masses (0.68 and 0.44 M _Jup , respectively). Notably, the gas and dust disk masses appear to evolve on different timescales. This is evidenced by the median gas-to-dust mass ratio, which decreases from 122 in the youngest disks (<1 Myr) to 46 in Lupus disks, and then increases to 120 in the Upper Sco disks. The median gas disk sizes range between 74 and 110 au, suggesting that typical gas disks are much smaller than those of well-studied, massive disks. Population synthesis models suggest that magnetohydrodynamic wind-driven accretion can reproduce median disk properties across all three regions, when assuming compact disks with a declining magnetic field over time. In contrast, turbulent-driven models overestimate gas masses of >1 Myr disks by an order of magnitude. Here, we discuss the program’s motivation, survey design, sample selection, observation and data calibration processes, and highlight the initial results.